LYNGBYA SP.: A SUITABLE CYANOBACTERIUM FOR HARVESTING ANTIMICROBIAL COMPOUNDS - Kumar, Maheep (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Lyngbya spp. is one of the most efficient groups of secondary metabolite producers and is very important from pharmaceutical point of view. Among its various species, majuscula is the major producers of commercially important biomolecules. Several species have been isolated and screened from the marine in the past decades. Although the chance of isolating a novel LyngbyaÂ strain from a marine habitat, which would produce new biologically active metabolites, has increased, but rediscovery has also important aspect. The most relevant reason for discovering novel secondary metabolites is to circumvent the problem of resistant pathogens, which are no longer susceptible to the currently used drugs. Existence of Lyngbya has been reported in the hitherto untapped brackish ecosystem. Marine Lyngbya are efficient producers of new secondary metabolites that show a range of biological activities including antibacterial, antifungal, anticancer, insecticidal and enzyme inhibitor. Bioactive compounds from marine Lyngbya possess distinct chemical structures that may form the basis for synthesis of new drugs that could be used to combat resistant pathogens. Â Â Keywords: Lyngbya Â· Bioactive compounds. Antibacterial. Antifungal. Secondary metabolites. Â